2016
DOI: 10.3390/ijms17050707
|View full text |Cite
|
Sign up to set email alerts
|

G Protein-Coupled Receptor Signaling in Stem Cells and Cancer

Abstract: G protein-coupled receptors (GPCRs) are a large superfamily of cell-surface signaling proteins that bind extracellular ligands and transduce signals into cells via heterotrimeric G proteins. GPCRs are highly tractable drug targets. Aberrant expression of GPCRs and G proteins has been observed in various cancers and their importance in cancer stem cells has begun to be appreciated. We have recently reported essential roles for G protein-coupled receptor 84 (GPR84) and G protein subunit Gαq in the maintenance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 155 publications
(195 reference statements)
1
43
0
Order By: Relevance
“…Several studies have demonstrated a central role for GPCRs such as GPR84, WNT, S1P, or CXCR4 in HSC maintenance (Doze and Perez, 2013;Lynch and Wang, 2016), and dysregulation of these pathways can have detrimental consequences, including malignant transformation. Because each GPCR is expected to stimulate multiple and highly interconnected cytoplasmic signaling pathways, largely through activation of AKT/MTOR, MAPKs, Hippo, or the Wnt/β-catenin signaling pathways, they can influence a wide array of biological responses (Laplante and Sabatini, 2012;Yu et al, 2012;O'Hayre et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated a central role for GPCRs such as GPR84, WNT, S1P, or CXCR4 in HSC maintenance (Doze and Perez, 2013;Lynch and Wang, 2016), and dysregulation of these pathways can have detrimental consequences, including malignant transformation. Because each GPCR is expected to stimulate multiple and highly interconnected cytoplasmic signaling pathways, largely through activation of AKT/MTOR, MAPKs, Hippo, or the Wnt/β-catenin signaling pathways, they can influence a wide array of biological responses (Laplante and Sabatini, 2012;Yu et al, 2012;O'Hayre et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…GPCR are transmembrane receptors that become activated upon the binding of extracellular ligands, propagating signals to cells . Their functions in mediating cell signals are extensive and crucial.…”
Section: Short‐chain Fatty Acids (Scfa)mentioning
confidence: 99%
“…GPCRs respond to a wide range of extracellular signals and regulate various cellular and physiological processes, including hormone regulation, vision, immune responses, neuronal communication, and behavior [2]. Overwhelming evidences have demonstrated that GPCRs and their downstream signaling targets play critical roles in cancer initiation and progression by regulating signal transduction and cellular processes (including cell proliferation, apoptosis, stress signals, immune escape, invasion, angiogenesis and metastasis, ion and nutrient transport and migration) [3,4]. It has also been demonstrated that diverse GPCRs were overexpressed in a variety of tumors [5].…”
Section: Introductionmentioning
confidence: 99%